Open-Tip Carbon Nanotubes for Enhanced Methane Adsorption Performance: A Comparative Study - Yanyan Feng; Yanjie Li; Wen Yang; Di Yang; Guangyuan Ye; Shufen Zhang (Journal of Nanotechnology)
A series of open-tip carbon nanotubes (CNTs) were obtained by HNO3 modification with various concentrations of as-prepared carbon nanotubes via the CVD method, and this work aimed at investigating the structural features of open-tip CNTs for the methane capability. Modified CNTs had higher specific surface area and larger total pore volume, and importantly, greater micropore volume was obtained through HNO3 modification of the as-prepared CNTs. The remarkably high methane adsorption capacities were measured on the modified CNTs under pressure ranges of 0∼4.0 MPa at 298 K. The resulted H-CNT, which exhibited highest specific surface area and micropore volume, showed high methane uptake of 26.15 mg/g from the D-A model. This value was nearly as twice as the methane uptake of original CNTs (13.62 mg/g), along with an initial adsorption heat of 19.4 kJ/mol at lower coverage and 9.5 kJ/mol at higher methane coverage for H-CNT, indicating the physical nature for methane adsorption over open-tip CNTs.